Virulence Factors of Clostridioides (Clostridium) difficile Linked to Recurrent Infections - Laura Tijerina-Rodríguez; Licet Villarreal-Treviño; Rayo Morfín-Otero; Adrián Camacho-Ortíz; E. Garza-González (Canadian Journal of Infectious Diseases and Medical Microbiology)
From 20 to 30% of Clostridioides (Clostridium) difficile infection (CDI), patients might develop recurrence of the infection (RCDI) and, after the first recurrence, the risk of further episodes increases up to 60%. Several bacterial virulence factors have been associated with RCDI, including the elevated production of toxins A and B, the presence of a binary toxin CDT, and mutations in the negative regulator of toxin expression, tcdC. Additional factors have shown to regulate toxin production and virulence in C. difficile in RCDI, including the accessory-gene regulator agr, which acts as a positive switch for toxin transcription. Furthermore, adhesion and motility-associated factors, such as Cwp84, SlpA, and flagella, have shown to increase the adhesion efficiency to host epithelia, cell internalization, and the formation of biofilm. Finally, biofilm confers to C. difficile protection from antibiotics and acts as a reservoir for spores that allow the persistence of the infection in the host. In this review, we describe the key virulence factors of C. difficile that have been associated with recurrent infections.